2009
DOI: 10.1007/s10517-010-0807-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High Power Terahertz Irradiation on Platelet Aggregation and Behavioral Reactions of Albino Rats

Abstract: Intensive terahertz irradiation at the nitric oxide emission and absorption spectrum frequencies (150.176-150.664 GHz) applied for 60 min to male albino rats subjected to acute immobilization stress enhanced platelet aggregation and induced signs of depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 3 publications
0
20
0
Order By: Relevance
“…To date, the only THz bioeffects study performed on mice was conducted in 2008 by Bondar et al [156]. Similar to their work where they used a rat model [153], this group postulated that THz radiation exposures may cause behavioral effects (i.e. anxiety) in mice.…”
Section: Rats (Rattus Norvegicus) Study 1 In 2008 Kirichuck Et Al mentioning
confidence: 96%
See 2 more Smart Citations
“…To date, the only THz bioeffects study performed on mice was conducted in 2008 by Bondar et al [156]. Similar to their work where they used a rat model [153], this group postulated that THz radiation exposures may cause behavioral effects (i.e. anxiety) in mice.…”
Section: Rats (Rattus Norvegicus) Study 1 In 2008 Kirichuck Et Al mentioning
confidence: 96%
“…Similar to their 2008 work, Kirichuk et al conducted a second study to investigate whether THz irradiated albino rats exhibited both enhanced platelet aggregation and behavioral alterations (i.e. depression) [153]. To test this hypothesis, rats were exposed to THz radiation using a microwave generator: 0.15 THz, 3 mWcm −2 , and exposure durations of 15, 30 or 60 min (Table 1).…”
Section: Rats (Rattus Norvegicus) Study 1 In 2008 Kirichuck Et Al mentioning
confidence: 98%
See 1 more Smart Citation
“…Behavioral alterations, such as increased levels of depression (0.15 THz, 3 mW/cm 2 [ 2 1 _ T D $ D I F F ] , 60 min) [94], were observed in a mouse model. Moreover, inflammatory responses and perturbation of the woundhealing process in mouse skin under THz irradiation have also been verified [95,96].…”
Section: Biological Effects: Increasing Concernsmentioning
confidence: 99%
“…It had been indicated that a high power THz irradiation (60-minutes) of MEAS of NO (150.176-150.664 GHz) in male rats under the acute immobilization stress, leads to a depression of a motion activity. This was evident from a statistically valid increase of a total time that animals had spent in Small Labyrinth, and a total time of animals' washing process [36,37].…”
Section: Thz Waves Effect On Nervous and Humoral Regulating Functionsmentioning
confidence: 95%